Phenotypic and genotypic resistance of Staphylococcus aureus in fresh meats marketed in Pernambuco, Brazil - Silva, Órion Pedro da; Leite, Denny Parente de Sá Barreto Maia; Barbosa, Iago Carvalho; Silva, Valdir Vieira da; Silva, Michelle Machado de Oliveira; Silva, Alane Pereira da; Moreira, Maria Aparecida Scatamburlo; Moura, Andrea Paiva Botelho Lapenda de; Barros, Mércia Rodrigues; Mota, Rinaldo Aparecido (Food Science and Technology, 2025)
Antimicrobial resistance is a challenge for public health, exacerbated by the indiscriminate use of these agents in humans and animals. Staphylococcus aureus, frequently found in fresh meat, poses a considerable risk due to its ability to transfer resistance genes. This study assessed the phenotypic and genotypic resistance profiles of Staphylococcus aureus isolated from 120 samples of beef, pork, and chicken sold in Recife, Pernambuco, Brazil. Samples were collected from markets, butcher shops, and street markets. Phenotypic identification was conducted using catalase tests and Gram staining, with confirmation through polymerase chain reaction (PCR) by amplifying the nuc gene. The resistance profile was evaluated using the disk diffusion method for 21 antimicrobials, following Clinical and Laboratory Standards Institute guidelines. In contrast, the resistance genes blaZ, mecA, mecC, norA, norC, tet(38), and msrA were analyzed by PCR. Among the 152 Staphylococcus spp. colonies isolated, 6.67% (10/152) were confirmed as S. aureus. Of these, 70% (7/10) were isolated from pork and 30% (3/10) from chicken, with no detection in beef samples. All isolates exhibited multidrug resistance, showing universal resistance to penicillin, rifampin, tetracycline, doxycycline, erythromycin, clindamycin, and linezolid. Genotypically, all isolates carried the norC gene, while 90% (9/10) harbored tet(38), and 60% (6/10) tested positive for norA and blaZ. No detection of mecA, mecC, or msrA was observed. These results underscore the urgent need for health education promoting the rational use of antimicrobials and coordinated actions between human and animal health sectors to mitigate antimicrobial resistance, which poses a serious threat to public health.